La protection d'un réseau local contre les attaquesLa mise en place le firewall - Hemici, maroua; Senigra, Safa (university of eloued جامعة الوادي, 2014)
Our project boils down to set up local network protected from external factors by a firewall .the firewall I sa program or device that prevent hackers and some type of malware from access to the computer through a network or through the internet. it performs by analyzing the information flow the internet and decide blocked or allowed to get into the networkأو من إحدى الشبكات، ثم یقوم إما بحظرھا أو السماح بھا للوصول إلى الكمبیوتر.
licence mimore informatique
Keywords: الشبكة المحلیة، الاختراق، الجدار الناري، الحمایة; Local network(LAN ),firewall, security